1996
DOI: 10.2307/4088898
|View full text |Cite
|
Sign up to set email alerts
|

Old Nest Material in Nest Boxes of Tree Swallows: Effects on Nest-Site Choice and Nest Building

Abstract: ABSTR•CT.-In natural cavities, old nest material accumulates with successive use, thereby reducing the size of the cavity, and allowing the numbers of certain haematophagous ectoparasites to increase. For this reason and because researchers studying birds breeding in nest boxes typically remove old nests from boxes, the results of such studies have been questioned. The accumulation of old nest material might affect nest-site selection and nest building by hole-nesting birds, so we tested this hypothesis by man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 33 publications
0
35
0
Order By: Relevance
“…increased ectoparasite and predator pressure, was not high, or was even decreased by the experimental procedures used. In studies where old nests were heat-treated, birds were found avoiding ectoparasites, and not the nest material itself (Oppliger et al 1994, Rendell & Verbeek 1996b, but Orell et al 1993). However, several other studies demonstrated that ectoparasite abundance did not differ between nests built in sites with or without an old nest (Table 4).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…increased ectoparasite and predator pressure, was not high, or was even decreased by the experimental procedures used. In studies where old nests were heat-treated, birds were found avoiding ectoparasites, and not the nest material itself (Oppliger et al 1994, Rendell & Verbeek 1996b, but Orell et al 1993). However, several other studies demonstrated that ectoparasite abundance did not differ between nests built in sites with or without an old nest (Table 4).…”
Section: Discussionmentioning
confidence: 99%
“…In the European Starling, for whom an avoidance of sites with old nest material was found in similar experiments, an additional experiment controlling for nest site depth revealed no preferences in relation to presence of old nests (Mazgajski 2003). Two similar types of experiments were carried out on Tree Swallows, but only the results of the first were presented, when nest site depth was not taken into consideration (Rendell & Verbeek 1996b Table 2. Effect of old nest material on nest site choice of hole nesting bird species.…”
Section: Nest Site Choicementioning
confidence: 96%
See 3 more Smart Citations